(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Organizational culture is a very debating area from the last few years in the world. Most of the research studies are conducted in the western countries and they adopted their own religious and societal values in their organizational culture, whereas, less researches are done on Islamic perspectives. Therefore, current study aims at finding values cover the Islamic perspectives at workplace. In order to meet the objectives on the study a sample of 328 employees was selected purposively comprising of employees working at private sector institutions at Peshawar. A total of 400 self-developed questionnaires were distributed, whereas, 312 were returned back, which were analyzed with the help of SmartPLS 4.0. The developed instrument was confirmed to be valid and reliable. The present study signifies that Islamic organizational culture (belief /trust on ALLAH, coordination, mutual trust, hardworking, absolute Sincerity, time for prayer and accountability) brings 89% change in Islamic work performance of employees of private universities of Khyber Pakhtunkhwa. The result of this study communicates significance of the Islamic organizational culture on Islamic work performance. In light of the results of the current study and previous research study results, it is safe to say that the organization may develop a good work environment which is based on belief /trust on ALLAH, coordination, mutual trust, hardworking, absolute sincerity, time for prayer and accountability to ensure a pleasant Islamic organizational culture to achieve better results.